The reality of the political participation of Syrian women in the current war Between (2011-2017) - أبو حمدان, ماجد; ديابي, حنان طارق (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The political participation of women is a true embodiment of the concept of citizenship and the values of democracy. Despite the gains made by women in Syria in the fields of education, work and health, they have not made similar progress in the political arena. Their participation in politics, public affairs and decision-making centers is still below the required level For political, social and historical reasons, in addition to the gap between the Constitution and national legislation on the one hand, and international conventions, resolutions and recommendations on the other hand, and the empowering reality of Syrian women has not received the required attention. Based on the above, the research aims to explore the truth about the political reality of women and their role in the political decision-making and decision-making process in Syria, especially in light of the current war that the country has been going through from 2011 to today, and the research aims to find out the deficiencies responsible for limiting the activation of their participation. Politically, and whether this defect - if proven by the study - is due to the legal systems of these political entities, or because Syrian women do not possess personal qualifications that enable them to enter the political arena, or because of the military reality's control over the course of the Syrian reality, which in turn affected the political presence of women, or because of variables Others crystallized by the results of this scientific research.